PARTISIPASI MASYARAKAT DALAM PELESTARIAN BUDAYA LOKAL TEMBANG MACAPAT PADA PROGRAM SIARAN RADIO KOMUNITAS ANGKRINGAN YOGYAKARTA - irawinnie rizky wahyu kusuma (Jurnal Ilmiah Dinamika Sosial, 2018)
ABSTRACTThe research discusses the preservation of local culture on Angkringan Community Radio through Macapat cultural programs, and community participation in the macapatan broadcast program. Research location in the village Timbulharjo, Sewon - Bantul, Yogyakarta.The analysis was conducted using qualitative research case study approach. Qualitative research methods describe the analysis with the socio- cultural and historical time and according to the conditions in which research occurs, analysis also combines collective participation theory with discusses. Methods of data collection conducted in this research include in-depth interviews and direct observation by reviewing the location of Community Radio Angkringan in Yogyakarta.The results of the preservation local culture with macapatan culture program and community participation. The researcher discovery of Angkringan community radio listeners macapatan particular at the age of 40 – 60 years old. Gender the radio listener more man than women. The conclusion having difference in age and gender segments. Shows the community radio administrator do not yet have clarity about the concept of the target market, focus of administrator only on the content program.Public participation occurs in the production process includes a process of making decisions about broadcast content, duration, and shcedule of the broadcast program. Community are actively involved in learning ti manage and organize broadcast.